Higher Fit-fOR-The-Aged (FORTA) scores comprising medication errors are associated with impaired cognitive and physical function tests in the VALFORTA trial - Pazan, Farhad; Burkhardt, Heinrich; Weiß, Christel; Wehling, Martin (Drugs & aging, 2019)
BackgroundThe Fit fOR The Aged (FORTA) list, a drug classification combining positive and negative labelling of drugs, has been clinically (VALFORTA-trial) validated to improve medication quality and clinical endpoints.ObjectiveThe objective of this study was to determine the association of medication quality with functional abilities tested in cognitive and physical function tests.Patients and MethodsData from the prospective, randomized controlled VALFORTA trial on 409 geriatric (mean age 81.53 years) in-hospital patients were tested for associations between the FORTA score (sum of over- and under-treatment errors) on admission and cognitive and physical function tests. Univariate and multivariate linear correlations corrected for age, sex, number of medications, number of chronic conditions, and body mass index as well as comparisons between high and low FORTA-score (cut-off 3) patients were performed.ResultsThe FORTA score was significantly correlated with Instrumental Activities of Daily Living (p < 0.0001), the Tinetti test (p < 0.002), Essen Questionnaire on Age and Sleepiness (p < 0.0001), Mini-Mental State Examination (p < 0.0001), and handgrip strength (p < 0.04) in the univariate analysis, and with Instrumental Activities of Daily Living (p < 0.003), the Tinetti test (p < 0.003), and the Essen Questionnaire on Age and Sleepiness (p < 0.0001) in the multivariate analysis. Effect size was weak for Instrumental Activities of Daily Living (R-squared = 0.12) and the Tinetti test (R-squared = 0.03) and medium for the Essen Questionnaire on Age and Sleepiness (R-squared = 0.22). Significant differences between patients with high and low FORTA scores were found for Instrumental Activities of Daily Living, the Tinetti test, mini-nutritional assessments, Mini-Mental State Examination, Essen Questionnaire on Age and Sleepiness, and the Geriatric Depression Scale. All significant tests revealed that higher FORTA scores (lower medication quality) were associated with less favorable test outcomes.ConclusionsThe FORTA score is associated with relevant aspects of comprehensive geriatric assessment, underlining the importance of medication quality for the functional and cognitive well-being of older patients.Trial Registration NumberDRKS00000531.